Dog man : the scarlet shedder - Pilkey, Dav, 1966- (New York : Scholastic / Graphix, 2024)
"P.U.! Dog Man got sprayed by a skunk! After being dunked in tomato juice, the stink is gone but the scarlet red color remains. Now exiled, this spunky superhero must struggle to save the citizens who shunned him! Will the ends justify the means for Petey, who's reluctantly pulled back into a life of crime in order to help Dog Man? And who will step forward when an all-new, never-before-seen villain unleashes an army of A.I. robots?"--
Ages 7 and up
Grades 2-3
Keywords: Dog Man -- (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Humorous stories; Adventure stories